UPAYA INKULTURASI LITURGI TERHADAP PRAKTIK RITUAL SIRAMAN PADA TRADISI MITONI - Segu, Yosef Irianto (Jurnal Orientasi Baru, 2017)
Salvation is the prime goal of human life. Mitoni in Javanese culture is a tradition to seek for a help for mother and her child in her 7th month pregnancy to give birth safely. Catholic Church proclaims salvation for all people also through some rites. Naturally those rites offered by the Catholic Church shall have relevance to people rooted in their culture. It is important that there is an harmonious encounter between culture and those rites as well as a liturgy that reflects mutual understanding and complementarity between Christian faith and culture, especially through inculturation. That encounter seeks to find a new meaning of life enlightened by faith. In the tradition of Mitoni this shall occur through its ritual of siraman and liturgy that accompanies. New meaning points to an experience of salvation in different form and content rooted in a culture. How far an inculturation could help facilitate?